Thoughts on Haptic Architecture By a Perceptual Psychologist - Howard C. Hughes (Oz, 2008)
Like most people, I do not know much about architecture, but I spend a great deal of time in buildings. I was therefore both intrigued and a little intimidated when I was asked by the editors of Oz to write an article on "haptic architecture."